SMG451 : Human resource management in sport and recreation / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course introduces the principles and practices of human resources management within an organization. It encompasses a comprehensive set of functions such as human resources planning, job analysis, the process of recruitment, screening, training, designing performance appraisals and compensation system. It also examines the human resources aspects of the Industrial Relations Acts 1967, and the Sport Development Acts 1997 and their relationship to sport and recreation organization